2022
DOI: 10.1038/s41419-022-04649-4
|View full text |Cite
|
Sign up to set email alerts
|

Metformin suppresses the growth of colorectal cancer by targeting INHBA to inhibit TGF-β/PI3K/AKT signaling transduction

Abstract: Multiple evidence shows that metformin serves as a potential agent for Colorectal Cancer (CRC) treatment, while its molecular mechanisms still require detailed investigation. Here, we revealed that metformin specifically suppressed the proliferation of CRC cells by causing G1/S arrest, and INHBA is a potential target for metformin to play an anti-proliferation effect in CRC. We verified the oncogene role of INHBA by knocking down and overexpressing INHBA in CRC cells. Silencing INHBA abrogated the cell growth,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 49 publications
1
29
0
Order By: Relevance
“…Notably, there were 772 overlap DEGs in the two cell lines, including Cyclin Dependent Kinase Inhibitor 1B ( CDKN1B ), Inhibin Subunit β A ( INHBA ), Ras Homolog Family Member U ( RHOU ), BTG Anti-Proliferation Factor 1 ( BTG1 ), Transducer Of ERBB2, 1 ( TOB1 ), N-Myc Downstream Regulated 1 ( NDRG1 ), MAX Network Transcriptional Repressor ( MNT ), MAX Interactor 1, Dimerization Protein ( MXI1 ), and Ajuba LIM Protein ( AJUBA ), which have been reported to be involved in the cell cycle and proliferation [ 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ]. Intriguingly, the GO analysis showed that the overlap genes were highly associated with the G1/S transition of the mitotic cell cycle, intrinsic apoptotic signaling pathway, and negative regulation of growth and DNA replication initiation ( Figure 7 G), and the KEGG analysis showed that they were significantly related to cell cycle and protein processing in the endoplasmic reticulum ( Figure 7 H).…”
Section: Resultsmentioning
confidence: 99%
“…Notably, there were 772 overlap DEGs in the two cell lines, including Cyclin Dependent Kinase Inhibitor 1B ( CDKN1B ), Inhibin Subunit β A ( INHBA ), Ras Homolog Family Member U ( RHOU ), BTG Anti-Proliferation Factor 1 ( BTG1 ), Transducer Of ERBB2, 1 ( TOB1 ), N-Myc Downstream Regulated 1 ( NDRG1 ), MAX Network Transcriptional Repressor ( MNT ), MAX Interactor 1, Dimerization Protein ( MXI1 ), and Ajuba LIM Protein ( AJUBA ), which have been reported to be involved in the cell cycle and proliferation [ 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ]. Intriguingly, the GO analysis showed that the overlap genes were highly associated with the G1/S transition of the mitotic cell cycle, intrinsic apoptotic signaling pathway, and negative regulation of growth and DNA replication initiation ( Figure 7 G), and the KEGG analysis showed that they were significantly related to cell cycle and protein processing in the endoplasmic reticulum ( Figure 7 H).…”
Section: Resultsmentioning
confidence: 99%
“…Metformin has displayed anticancer effects towards different types of cancer cells in an in vitro cell study, with Nrf2, YAP, HIF-1α, HMGB1, TGF-β1, glycolysis and glutamine metabolism being proposed action targets at a cellular level [ 14 , 18 , 19 , 20 , 21 , 22 , 23 ]. However, the in vivo anticancer effects of metformin vary and depend on the accompanying situations.…”
Section: Discussionmentioning
confidence: 99%
“…Reduction in circulating insulin and activation of 5′-AMP-Activated Protein Kinase (AMPK) are two reported anticancer mechanisms of metformin [ 16 , 17 ]. Moreover, Nuclear Factor Erythroid 2-Related Factor 2 (Nrf2), Yes-Associated Protein (YAP), Hypoxia-Inducible Factor-1α (HIF-1α), High-Mobility Group Box 1 (HMGB1), Transforming Growth Factor-β1 (TGF-β1), glycolysis, glutamine metabolism and antitumor immunity have all been further highlighted as functional targets in the anticancer actions of metformin [ 14 , 18 , 19 , 20 , 21 , 22 , 23 ]. Regarding the pro-malignant effects of platelets and neutrophils, metformin inhibits both the release of NETs and hyper-activity of platelets [ 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…As one of the most used first-line drugs for T2DM, metformin also has anticancer effects ( Vancura et al, 2018 ; Cheng et al, 2021 ; Xiao et al, 2022 ). Here, our data indicated that metformin could alleviate the mitochondrial fission exerted by insulin resistance in cells.…”
Section: Discussionmentioning
confidence: 99%